Management of origin and traceability of organic export products in Peru - Altamirano Flores, Ernesto (2021)
The objective of the study was to explain through a model, the influence of chemical compounds in determining the origin and traceability of organic export products, to generate confidence and security in the choice of organic food in consumers, tracing it as purpose the determination of stable isotopes to know the origin and traceability of organic export products, in order to generate confidence and security in the choice of food in consumers. The research methodology was quasi-experimental - descriptive - correlational – explanatory, in addition, data from experiments carried out were used, where the surveys and questionnaires applied in the interview have provided the information that was processed through SPSS program and LISREL for factor analysis. It has been proven that in the studied model the influencing factors originality, traceability and the composition of the food